Adapting the product group-specific nutritional functional units to the Spanish context - Torán-Pereg, Paula; Kyttä, Venla; Pardo, Guillermo; Saarinen, Merja (Springer Nature, 2025)
Purpose Nutritional aspects have recently been integrated into the life cycle assessment (LCA) of foods through the use of nutrient indices as functional units (nFU). In this study, we develop the nFU indices for each product group presented in the Spanish plate model, by adapting the approach introduced in our previous studies into a Spanish context. Methods The product grouping followed the Spanish plate model covering protein-rich foods, sources of carbohydrates, vegetables and fruits, and fats. For each group, separate nFUs were created by identifying the most important nutrients for each product group, based on the nutrients obtained from them in the current Spanish food consumption. Finally, the new nFUs were showcased by conducting cradle-to-plate nLCA for the selection of typical Spanish foods. Results and discussion Adapting the method to formulate the nFUs to different target population led to different selection of nutrients being included in the indices for each product group, highlighting the need to tailor the methodology depending on the population under study. The nLCA results demonstrated the importance of integrating nutritional aspects into comparative LCAs of foods in all the studied product groups, also including the new product group of fats, which was the first time used in nLCA in this study. Conclusions The results demonstrated that the product-group-specific approach is a systematic and reproducible method to formulate nFU indices and that it can be consistently adapted also to other target populations with relevant data available. For more extensive coverage of health aspects in LCA, the inclusion of non-nutrient compounds should be promoted.
Keywords: NLCA; nutrient index; functional unit; sustainable nutrition; dietary shift; meals